1993
DOI: 10.1007/bf00168772
|View full text |Cite
|
Sign up to set email alerts
|

Identification of endothelial H1, vascular H2 and cardiac presynaptic H3 receptors in the pithed rat

Abstract: In pithed and vagotomized rats the effects of the H3 receptor agonist R-(-)-alpha-methylhistamine, the H1 receptor agonist 2-(2-thiazolyl)ethylamine and the H2 receptor agonist dimaprit on basal diastolic blood pressure, basal heart rate and the electrically induced rise in heart rate were examined. Basal diastolic blood pressure was not altered by low, but increased by high doses of R-(-)-alpha-methylhistamine; the latter effect was not affected by selective H1, H2 or H3 receptor antagonists and by prazosin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 20 publications
4
20
0
Order By: Relevance
“…The results suggest that basal cyclic GMP levels are almost exclusively due to spontaneous release of NO. The HI receptor agonist, AEP, was capable of eliciting contraction in the presence of these basal levels of cyclic GMP and interestingly, although HI receptors are also reported to be present on endothelial cells in some blood vessels (Chen & Suzuki, 1989;Malinowska & Schlicker, 1993) we did not observe a significant change in cyclic GMP levels when AEP was added to the tissue. Basal cyclic GMP levels appear to modulate contractions however, since significantly larger contractions were obtained in the presence of either L-NMMA or HbO.…”
Section: Discussionmentioning
confidence: 50%
“…The results suggest that basal cyclic GMP levels are almost exclusively due to spontaneous release of NO. The HI receptor agonist, AEP, was capable of eliciting contraction in the presence of these basal levels of cyclic GMP and interestingly, although HI receptors are also reported to be present on endothelial cells in some blood vessels (Chen & Suzuki, 1989;Malinowska & Schlicker, 1993) we did not observe a significant change in cyclic GMP levels when AEP was added to the tissue. Basal cyclic GMP levels appear to modulate contractions however, since significantly larger contractions were obtained in the presence of either L-NMMA or HbO.…”
Section: Discussionmentioning
confidence: 50%
“…while the electrically induced increases in blood pressure andin heart rate are inhibited at 0.01 -10 pmol/kg i.v. [ 14,15]. By comparing MHA dose ranges in our and other studies, it can be concluded that a high dose range is required to achieve protection of the gastric mucosa.…”
Section: Discussionmentioning
confidence: 56%
“…Body temperature was kept constant at 37 + 1°C. Following pithing, blood pressure was routinely raised to 80-100 mmHg by infusion of vasopressin (0.04 -0.4 i.u., kg-1 min-') into the right femoral vein (since vasopressor/vasodepressor effects are more marked at a higher level of blood pressure; see, e.g., Malinowska & Schlicker, 1993). After 15-30 min of equilibration, during which the cardiovascular parameters were allowed to stabilize, experiments were performed.…”
Section: Methodsmentioning
confidence: 99%